Literature Review: Urgensi dan Implikasi Strategi Pemasaran Hijau - Muhammad Luthfi Hamdani (Jurnal Manajemen Bisnis Era Digital, 2025)
This study discusses the urgency of green marketing strategies and practices due to changes in consumer behavior trends. Currently, environmental sustainability issues are a major concern for society, not interacting in their product and service consumption activities. This study was conducted using a qualitative method, namely a literature review. Of the 15 article titles described, most of them show that the implementation of environmentally friendly marketing strategies brings positive benefits to businesses. Specifically, what is studied in this study is its influence on environmentally friendly purchasing decisions, customer loyalty and brand image enhancement. These findings can be practical recommendations for business actors and marketing practitioners to develop various environmentally friendly product and service innovations and carry out innovative green marketing practices in the future. So that they are able to gain benefits in the form of increased sales, customer loyalty and positive brand image as well as contributions to environmental sustainability or desires.